STRATEGI NEGOSIASI ANTAR FRAKSI-PRO DAN KONTRA PEMERINTAH DALAM PENYESUAIAN KEBIJAKAN PADA RUU PEMILUTAHUN 2017 - Edik Prayitno (Oratio Directa (Prodi Ilmu Komunikasi), 2021)
ABSTRACT The Election Bill is a guideline for the elections, namely the Komisi Pemilihan Umum (KPU), Badan Pengawasan Pemilu (Bawaslu) during the implementation of the 2019 General Election. At this stage there were differences of opinion between the existing factions. The disagreement of opinion is due to the existence of between the government factions and cons or who are members of a government coalition with factionsthat are not included in the government coalition. The factions supporting the government are the Party PDI-P, Golkar, NasDem, Hanura, PKB, PPP. While parties that are not supporters of the government are Gerindra, PKS, PAN. While Democrats do not determine the attitude. Functional theory of group communication views processes as decision instructors, emphasizing the relationship between communication quality and output quality. Communication groups do a number of things or function in a number of ways todetermine or decide group outcomes. The final result of the plenary session of the five crucial issues was successfully decided through the lobby and negotiation of various matters which became the debate of variousfactions. Through the plenary session the fifth issue was successfully decided by voting. Keywords: Negotiation Strategy, RUU Election, policy adjustment